2020
DOI: 10.3389/fcell.2020.00852
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Targeting of HIPK2 Leads to Acetylation-Dependent Chromatin Decondensation

Abstract: The protein kinase homeodomain-interacting protein kinase 2 (HIPK2) plays an important role in development and in the response to external cues. The kinase associates with an exceptionally large number of different transcription factors and chromatin regulatory proteins to direct distinct gene expression programs. In order to investigate the function of HIPK2 for chromatin compaction, HIPK2 was fused to the DNA-binding domains of Gal4 or LacI, thus allowing its specific targeting to binding sites for these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…There is support for this model, since HIPK2 can associate with the Polycomb protein Pc2/CBX4, which is part of the Polycomb repressive complex 1 (PRC1) ( Roscic et al 2006 ). Another recent study used HIPK2 tethered to chromatin to directly address its ability to modulate chromosome compaction, where chromatin bound HIPK2 led to decreased Histone 3 Lysine 27 trimethylation (H3K27me3), an epigenetic mark normally associated with transcriptional repression and formation of heterochromatin ( Haas et al 2020 ). Thus, our findings of phenotypes associated with dysfunction of TrxG/PcG and previous work suggest that Hipks may play roles in regulating chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…There is support for this model, since HIPK2 can associate with the Polycomb protein Pc2/CBX4, which is part of the Polycomb repressive complex 1 (PRC1) ( Roscic et al 2006 ). Another recent study used HIPK2 tethered to chromatin to directly address its ability to modulate chromosome compaction, where chromatin bound HIPK2 led to decreased Histone 3 Lysine 27 trimethylation (H3K27me3), an epigenetic mark normally associated with transcriptional repression and formation of heterochromatin ( Haas et al 2020 ). Thus, our findings of phenotypes associated with dysfunction of TrxG/PcG and previous work suggest that Hipks may play roles in regulating chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that hHIPK2 can interact with and phosphorylate CBX4/Pc2, a PRC1 component homologous to D. melanogaster Polycomb (Pc), in the early response to DNA damage, however this interaction was found to promote transcriptional silencing in this context [57]. More recently, the same group has found that under otherwise normal conditions, targeting hHIPK2 to specific DNA regions causes de- condensation and de-repression of chromatin at those genomic loci [58]. The latter result supports our finding of normally repressed homeotic genes becoming de-repressed in response to hHIPK expression, however interactions between Hipks and PRC1 or PRC2 components that are important in the context of normal development have not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…After reaching 60–70% confluence Lipofectamine transfection with siScramble (10 nM) (D-001810-10-05, Dharmacon) and siRNAs targeting SIAH1 (10 nM) (#4427037, Thermo Fisher) and/or SIAH2 (10 nM) (#L-006561-00-0010, Dharmacon) was carried out for 48 h. One day after transfection in DMEM containing 10% FCS without penicillin/streptomycin, medium was exchanged to full media. The plasmids encoding HA-tagged p300, SIAH1 and SIAH2 [ 27 ] and GFP-lacI [ 31 ] were described and GFP-lacI-p300 (Addgene ID: 179270) was created. These plasmids were transiently transfected using linear PEI as published [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected as displayed in the figure legends. After 24 h cells were washed with PBS and fixed with 3.7% (v/v) formaldehyde for 10 min and further processed as described [ 31 ]. Nuclei were stained with Hoechst 33324 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%